PENGARUH BERMAIN KOLASE TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK - Nur Hamiza; Parni; Novi Cahya Dewi (Fakultas Tarbiyah Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
It is very important to optimize fine motoric development at the age of 5-6 years as an initial capital in stimulating children's writing skills needed for learning at the next education level. One of the activities that are effective in developing children's fine motor skills is through playing collages. This research was conducted using a quantitative approach to the type of quasi-experimental research. Data collection techniques using direct observation and documentation. The population in this study amounted to 20 children, namely the experimental class and the control class. The data analysis technique used was Mann Whitney U with the help of IBM SPSS Statistics 23. The results showed that: 1) The fine motor development of children in PAUD Darussalam before being treated was still low with the mean rank of the experimental class 11.65 and the mean rank of the control class 9.35. As for the results of the Mann Whitney calculation (pretest), it can be seen that Sig.> 0.05 is 0.364, so Ha is rejected and Ho is accepted. This means that there is no difference in the value of fine motoric development in the experimental class and the control class; 2) The fine motoric development of children after being treated in the experimental class with a mean rank of 15.50. while for the control class with a mean rank of 5.50. As for the results of the Mann Whitney (posttest) calculation, it can be seen that the value of Sig. <0.05 is 0.000, so Ha is accepted and Ho is rejected. This means that there are differences in the value of fine motoric development in the experimental class and the control class; 3) The effect of playing collage activities on fine motoric development of children aged 5-6 years can be completed based on the research design paradigm (O2-O1) - (O4-O3) with the results before being treated and after being given treatment, namely with a value of 29 with criteria positive. This means that playing collage affects the fine motoric development of children.